Metabolic syndromes, carbohydrate and lipid metabolism disorders in helminthic infections: review of the literature - E. A. Golovach; O. S. Fedorova; T. V. Saprina; V. V. Ivanov; E. A. Perina; Yu. V. Kovshirina; L. M. Ogorodova (Бюллетень сибирской медицины)
Metabolic syndrome is a common pathological condition based on an increase of the mass of visceral fat, insulin resistance with hyperinsulinemia, carbohydrate, lipid and protein disorders. The natural course of the metabolic syndrome can be affected by the presence of intercurrent diseases connected with metabolic disorder, and helminthic infections are among them. This review presents an analysis of the results of current epidemiological and experimental studies of metabolic syndrome and abnormalities of carbohydrate and lipid metabolism associated with helminth infections.